A17 LINEAR GROWTH IMPAIRMENT IN CANADIAN CHILDREN PRESENTING WITH NEW ONSET IBD: A MULTI-CENTRE INCEPTION COHORT STUDY. (1st March 2018) - Walters, T D; Mack, D R; Huynh, H Q; deBruyn, J; Jacobson, K; Otley, A; EL-MATARY, W; Deslandres, C; Sherlock, M; Seidman, E G; Bax, K; Critch, J; et al.
Abstract: Background: An important target in the management of pediatric inflammatory bowel disease (IBD) is normal linear growth and pubertal development. Greater awareness of IBD and more effective therapies are anticipated to reduce the prevalence of linear growth impairment as a complication of chronic intestinal inflammation. Aims: To evaluate the current magnitude of linear growth impairment at diagnosis in pediatric Crohn's disease (CD) and ulcerative colitis (UC). Methods: Since April 2014, the Canadian Children IBD Network (CIDsCANN) inception cohort study prospectively enrolled patients aged </= 17 years, presenting to 12 academic centers across Canada. Recommended assessment of linear growth at presentation includes height measurement, pubertal staging, ascertainment of pre-illness heights and mid-parental height (MPH) calculation. All growth parameters are standardized utilizing the Centers for Disease Control (CDC) 2000 reference tables. 'Deficit height z-score' was calculated using the formula: 'Predicted Height z-score' minus 'Actual Height z-score'. Results: Among the initial 800 participants (58% male; CD: 59%, UC: 30%, IBD-unclassified: 11%), median age at presentation was similar for the three disease sub-categories (12.9 yrs; IQR 10.8–15.0), but duration of symptoms prior to diagnosis was significantly longer in CD (5 months, IQR 3–12 months) vs. UC (3 months, IQR 1–6 months) (p<0.001). Macroscopic disease location based on Paris classification for UC was: 70% E4; 12% E3; 16 % E2 and for CD was: 58% L3; 23% L2; 18% L1. Linear growth impairment, based on historical growth parameters, occurred in 21% of CD patients (8% as the main presenting feature), and 3% of UC patients (but none as the main presenting feature). Predicted height z-scores (based on MPH) were normally distributed (mean 0.07, SD 0.8) with no difference noted between CD and UC patients. As shown in Table, the UC cohort had normal height at diagnosis, but in the CD cohort height was reduced compared to both the healthy population and predicted values. This was especially especially prominant among younger vs. older CD patients (p=0.05), despite similar symptom duration (median 5 months) prior to diagnosis (Table). Males demonstrated a greater deficit than females. Conclusions: Linear growth impairment still occurs prior to the recognition of Crohn's disease in young patients, but its magnitude is less than in previous eras. Deficit in Height Z-score based on the Mid-Parental Height calculation appears a useful metric in quantifying linear growth impairment. Funding Agencies: CH.I.L.D Foundation